2001
DOI: 10.1021/ma0110913
|View full text |Cite
|
Sign up to set email alerts
|

Association of κ-Carrageenan Induced by Cs+ Ions in Iodide Aqueous Solution:  A Light Scattering Study

Abstract: Light scattering (LS) investigations have additionally confirmed the intramolecular nature of the fundamental ordered conformation (single helix) of κ-carrageenan in aqueous 0.1 M NaI. The partial replacement of sodium with cesium ions induces a (thermoreversible) intermolecular association of the polysaccharide in the ordered conformation. The association-inducing effect can be observed already at the lowest investigated concentration of the cation. We found no significant change of the thermodynamic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
(101 reference statements)
1
31
0
1
Order By: Relevance
“…If we apply the theoretical model discussed previously by Vroege and accept that the hardcore diameter of KC is of 14 Å (based on the fact that the radius of the helix of KC in 0.1 M NaI is 7 Å as found from neutron and X-ray scattering measurements, Ramzi et al, unpublished), the effective diameter was calculated to be 37.81 Å (see Appendix). Considering that the κ-carrageenan in 0.1 M NaI has a persistence length of 35.6 nm, 25 we estimate the weight fraction for the isotropic-nematic transition at 4.7 wt % -4.8 wt %, respectively (see also Appendix). Indeed, these values are in the close agreement with the value that we found experimentally.…”
Section: Further Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we apply the theoretical model discussed previously by Vroege and accept that the hardcore diameter of KC is of 14 Å (based on the fact that the radius of the helix of KC in 0.1 M NaI is 7 Å as found from neutron and X-ray scattering measurements, Ramzi et al, unpublished), the effective diameter was calculated to be 37.81 Å (see Appendix). Considering that the κ-carrageenan in 0.1 M NaI has a persistence length of 35.6 nm, 25 we estimate the weight fraction for the isotropic-nematic transition at 4.7 wt % -4.8 wt %, respectively (see also Appendix). Indeed, these values are in the close agreement with the value that we found experimentally.…”
Section: Further Considerationsmentioning
confidence: 99%
“…24 Recently it has been found that κ-carrageenan helix in 0.1 M NaI has a persistence length of 35.6 nm. 25 Despite the progress made, the properties of liquid crystalline polymers are not fully understood yet theoretically. Liquid crystalline polymers (LCP's) can be approached theoretically with the basic model of the rigid rod.…”
Section: Introductionmentioning
confidence: 99%
“…The gelation mechanism of k-and i-carrageenans has been previously described and investigated (Cuppo, Reynaers, & Paoletti, 2002;Mangione, Giacomazza, Bulone, Martorana, & San Biagio, 2003;Viebke, Borgstro¨m, Carlsson, Piculell, & Williams, 1998;Yuguchi, Tha`nh, Urakawa, & Kajiwara, 2002); l-carrageenan appears not to gel in aqueous systems. Briefly, a random coil to helix conformational transition proceeds with aggregation of helical segments to rigid rod bundles, eventually forming a gel network.…”
Section: Introductionmentioning
confidence: 99%
“…127H1222) of weight-average molar mass M w = 1.79(±0.02) × 10 5 g mol −1 (as determined by wide-angle light scattering) was purified as previously described [6]. Aqueous solutions in mixed NaI/CsI salt (with constant 0.1 M iodide concentration and varying cesium mole fraction, the latter being defined as X Cs = [CsI]/([CsI] + [NaI]) were prepared according to a standard procedure [6]. A peristaltic pump in a closed circuit was used to filter the solutions (Millipore membrane, pore size 0.22 m) directly in the light scattering cell.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work [3,5], we stressed the fundamental role of the preparative procedures in order to obtain reproducible and reliable results when dealing with -carrageenan, due to the extreme sensitivity of the biopolymer to the physicochemical parameters applied and, in particular, because of the very marked tendency towards macromolecular aggregation. Recently [6], we demonstrated, by use of static light scattering, the possibility to accurately control the process of intermolecular association in -carrageenan solutions, ranging from conditions of very limited cluster formation up to conditions of extensive, time-dependent association. To this purpose, we applied the mixed-counterion method firstly employed by Borgström et al [7].…”
Section: Introductionmentioning
confidence: 99%